IMPLEMENTASI STRATEGI CSR (CORPORATE SOCIAL RESPONSIBILITY) MELALUI PROGRAM ICD (INTEGRATED COMMUNITY DEVELOPMENT) PADA PT TIRTA INVESTAMA AQUA PANDAAN - Badjamal, Abdul Kadir (Jurnal Ilmiah Mahasiswa FEB, 2018)
Manufacturing activities of the industry is directly tangent to the community. Companies are required to create a positive impact on the environment and society. One strategy that can be implemented is Corporate Social Responsibility (CSR). This study aims to reveal the mechanism of CSR implementation and also evaluate the implementation process that has been run starting in 2011. This research is a descriptive qualitative research. The focus of this research is on the data obtained through direct interview with the Sustainbility Development Department of PT Tirta Investama Pandaaan. The results of the evaluation of the CSR implementation process is still the problem faced by the company. The main problem that occurs is the excessive expectations of some communities in each program and there are groups who are on behalf of the wider community but carry a personal mission. The solution that can be done to overcome the problems of corporate CSR is to increase the intensity of communication with the community and conduct discussions with key stakeholders.Keywords: Corporate Social Responsibility, Implementation Strategy, Integrated Community Development